Daily Life for the Common People of China - Suleski, Ronald (Brill, 2018)
In this book Ronald Suleski introduces a new category of source material, ''chaoben'' 抄本, for understanding the lives of China's semi-literate masses before 1950. It links the documents now flooding the antiques markets in China, with the hopes and fears of China's people at the end of the pre-modern era.